As necessidades e expectativas das professoras-estudantes da pedagogia/parfor sobre sua formação docente frente aos desafios da prática profissional - Carvalho, Cristina Pereira (2014)
This job objectifies to comprehend the needs/expectations of professors/students of Pedagogy (BRAZIL, 2009) on its context of training when faced with obstacles in their professional practice. Focusing on the Theory of Social Representations/TRS, of Moscovici (1978), and in authors, who are dedicated in its training and professional practice, such as Rodrigues and Esteves (1993), Novoa (1992, 1995, 1999), Abdalla (2006, 2008, 2011, 2012) Freire (2007), among others. The research has evolved in the following steps: 1ª application of a questionnaire for 43 professors/students, with closed questions (32) open (4) and words to remember (4), integrated in a Project, more broadly related to the International Center of Social Representation ¿ CIERS-ed/FCC and to the Project OBEDUC/Capes; 2ª creation of the Focus Group for 08 of these teachers, developing the subject area in question; and 3ª semi-structured interviews with 04 teachers that had participated on the previous steps, with the intent of going over certain questions and intensifying them. Based on the data, the results anchored in two dimensions of analysis. On the formative dimension, these teachers showed the following needs: 1ª their own trajectory of formation; 2ª lack of previous training and/or knowledge (Academic basis); 3ª the problems with reconciling the training and work due to the ¿triple journey.¿ Indicated, as well, certain expectations, such as: a) the personal realization ¿ ¿to become somebody in life¿; b) the process of intellectual growth; c) personal appreciation ¿ strengthening the sense of belonging to the group. And, on the professional dimension, the results lead to the necessity to: 1ª reflect over the pedagogical practices and experience new practices learned during training. 2ª transform the theory onto practice, and the practice onto theory (theorize about the practice); 3ª to confront the job conditions. As far as professional expectations: a) value the professional realization; b) to better your performance and responsibility on the job; and c) to better the conditions of your job and on your career plans. Currently, it is noted that the implications of Pedagogy through the training and on the career of these professors-students, is strengthening the process of the reconstitution of identity of these professionals and allowing possibilities for them to meet the needs inside the school and/or outside the classroom.